Ultrathin thermally conductive yet electrically insulating exfoliated graphene fluoride film for high performance heat dissipation. (February 2020) - Vu, Minh Canh; Thi Thieu, Nhat Anh; Lim, Jung-Hyurk; Choi, Won-Kook; Chan Won, Jong; Islam, Md. Akhtarul; Kim, Sung-Ryong
Abstract: With the development of portable and flexible electronic devices, demends for high-performance thermal management materials with high thermal conductivity and electrical insulation are growing. Recently, graphene fluoride has received numerous attention from science community due to its high thermal conductivity and electrical insulation. Here, we report an advanced exfoliated graphene fluoride (EGF) film as a high performance heat spreader and thermal interface material for flexible electronic devices, which simultaneously exhibits ultrahigh thermal conductivity, excellent electrical insulation, and satisfactory flexibility. Commercially available graphite fluoride was directly exfoliated into graphene fluoride solution using ball milling method, followed by preparing ultrathin graphene fluoride films to take full advantage of graphene fluoride properties for heat dissipating applications. The resultant films show a tunable thermal conductivity by altering the thickness of films and show a superior in-plane thermal conductivity of 242 W m −1 K −1 and exceptional through-plane thermal conductivity of 21.8 W m −1 K −1 at the thickness of 10 μm. More interestingly, the graphene fluoride films possess excellent flexibility. The newly developed EGF film provides a creative opportunity for fabrication of multifunctional highly flexible materials, which may promote the development of heat dissipation materials in next generation flexible electronics. Graphical abstract: Image 1